A porous carbon material and its preparation method and application
Through the combination of ultra-fast ultra-high temperature sintering technology and seed inducers, the problems of high cost, low pollution and conductivity in the preparation of porous carbon materials are solved, and porous carbon materials with a high mesoporous proportion are prepared, which improves lithium-ion batteries The performance and process of the negative electrode material are simplified.
Patent Information
- Application Number
- CN202411186397.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-28
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-08-28
AI Technical Summary
Among the existing porous carbon materials preparation methods, the template method is costly and the removal process is complex. The activation method may pollute the environment and traditional high-temperature preparation leads to low conductivity, making it difficult to effectively control the pore structure and the degree of graphitization.
Using ultra-fast ultra-high temperature sintering technology combined with seed inducers, the high mesoporous porous carbon materials are prepared through the mixed carbonization, physical activation and ultra-fast ultra-high temperature sintering of carbon precursors and seed inducers, and the conductivity is improved. And simplify the process flow.
The preparation of porous carbon materials with high conductivity is realized, the process flow is simplified, the introduction of impurities is reduced, suitable for industrial applications, and the performance of the negative electrode materials of lithium-ion batteries is improved.
Smart Images

Figure CN118702098B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of carbon material preparation, and specifically relates to a method for preparing a porous carbon material and the porous carbon material prepared by the preparation method, and also provides the application of the porous carbon material as a matrix in a negative electrode material of a lithium ion battery. Background Art
[0002] Porous carbon materials have become one of the important choices for negative electrode materials of lithium-ion batteries due to their unique structural properties, such as high specific surface area, good conductivity, excellent chemical stability and mechanical strength. Simply put, the porous structure of porous carbon materials can provide more active sites, increase the contact area between the negative electrode materials of lithium-ion batteries and the electrolyte, and thus improve the charge and discharge performance of the battery. In addition, porous carbon materials usually have a high lithium storage capacity and good cycle stability, and they can provide a fast lithium ion diffusion path during the charge and discharge process.
[0003] According to the pore size, the pores in porous carbon materials can be divided into three categories: macropores (pore size > 50nm), mesopores (mesopores) (2nm≤pore size≤50nm), and micropores (pore size <2nm). At present, new silicon-carbon negative electrode materials mostly choose porous carbon as the matrix, mainly to deposit the silicon source in mesopores with a pore size of 2-10nm. This requires that the proportion of mesopores in porous carbon materials should be high, and micropores with a pore size less than 2nm should be as closed as possible (if the proportion of micropores is too high, it will reduce the deposition efficiency of active materials).
[0004] At present, the preparation methods of porous carbon mainly include template method and activation method. Among them, the template method uses a hard template (such as silicon, metal oxides, etc.) or a soft template (such as polymers, surfactants, etc.) as a sacrificial structure, fills the pores of the template with a carbon source material, and obtains porous carbon through carbonization and template removal. Although the template method can control the pore structure in an orderly manner, the template materials used in some methods are relatively expensive, and the template removal process (such as etching removal) may increase additional costs. The activation method processes the carbon source material under certain conditions through physical activation or chemical activation to produce a porous structure. Chemical activation uses chemical substances such as KOH and ZnCl2 as activators, which may pollute the environment and produce harmful gases during the activation process. Physical activation usually uses gases such as CO2 or water vapor as activators to activate and pore the carbon material at high temperatures (generally above 1000°C). Due to the high temperature, a long heating and insulation process is required, which leads to an increase in the proportion of micropores in the porous carbon material. In addition, the degree of graphitization of porous carbon materials prepared under traditional high temperatures is not high, which leads to low electrical conductivity of porous carbon, reducing the initial efficiency and rate performance of lithium-ion battery negative electrode materials.
[0005] Ultra-Fast Ultra-High Temperature Sintering (UHS) is a technology that uses high-power radiation to quickly heat, keep warm, and cool in an inert atmosphere to achieve fast and efficient sintering of materials. This technology is mainly based on the theory of Joule heat (the process of converting electrical energy into thermal energy when current flows through a resistor is called Joule heat): According to the Joule quantification, the heat generated by current passing through a conductor is proportional to the square of the current, the resistance of the conductor, and the power-on time. The current can be adjusted to achieve rapid heating of the object. For example, using graphite felt as a heating electrode, the heating rate can reach 10 3 ℃ / min~10 4 ℃ / min, the cooling rate can be as high as 10 4 ℃ / min, which can quickly increase the temperature of the object to be heated and effectively reduce energy consumption. There are cases where this sintering technology has been applied to the preparation of porous carbon materials, and a graphitization catalyst is used to increase the graphitization degree of the porous carbon and retain its porous structure. However, since the introduced catalysts are mostly metal catalysts, it is easy to introduce impurities into the porous carbon material, and subsequent acid washing, water washing and other steps are required to remove them, which is not environmentally friendly and the process is relatively complicated. Summary of the invention
[0006] In view of this, the primary purpose of the present invention is to provide a method for preparing a porous carbon material. During the preparation process of the porous carbon material, a seed inducer is introduced and combined with ultrafast ultra-high temperature sintering technology. The prepared porous carbon material not only has high electrical conductivity, but also has a high proportion of mesopores with a particle size of 2-10nm, which lays the foundation for the subsequent preparation of high-performance lithium-ion battery negative electrode materials.
[0007] In order to achieve the above object, the present invention adopts the following technical solutions:
[0008] The present invention first provides a method for preparing a porous carbon material, comprising the following steps:
[0009] Providing a mixed slurry containing a carbon precursor and a seed crystal inducing agent, and carbonizing the mixed slurry to obtain a pre-carbonized precursor material;
[0010] Physically activating the pre-carbonized precursor material to form pores, thereby obtaining a porous carbon precursor material;
[0011] The porous carbon precursor material is sintered by adopting ultrafast ultrahigh temperature sintering technology to obtain the porous carbon material.
[0012] In a further embodiment, the carbon precursor is a biomass carbon source or a resin carbon source;
[0013] Wherein, the biomass carbon source is selected from one or a mixture of two or more of coconut shells, straw, rice husks, wood, bamboo, bagasse, and nut shells;
[0014] The resin carbon source is selected from one or a mixture of two or more of furan resin, urea-formaldehyde resin, pyrimidine resin, phenol-formaldehyde resin, epoxy resin, polyoxymethylene methyl acrylate resin and polyacrylonitrile.
[0015] In a further embodiment, the seed inducer is selected from one or a mixture of two or more of graphene oxide, graphene, carbon nanotubes, and carbon fibers.
[0016] In a further embodiment, the mass ratio of the carbon precursor to the seed inducer is 20:1 to 300:1.
[0017] In a further embodiment, the gas activator used in the physical activation pore formation is water vapor or CO2;
[0018] And / or, the temperature of the physical activation pore formation is 800° C. to 1300° C., the activation time is 0.5 h to 6 h, and the flux of the gas activator is 0.1 L / min to 20 L / min.
[0019] According to a further solution, the sintering temperature of the ultrafast ultrahigh temperature sintering technology is 1000°C~3500°C, the heating time is 5s~30s, and the sintering time is 30s~600s.
[0020] The present invention further provides a porous carbon material, which is prepared by the preparation method as described above.
[0021] The present invention further provides a negative electrode material, comprising a porous carbon material prepared by the preparation method described above; the pores of the porous carbon material contain active materials.
[0022] In a further embodiment, the negative electrode material is a silicon-carbon composite material, and the active material is a silicon-carbon material;
[0023] And / or, the silicon carbon material is deposited in the pores of the porous carbon material by vapor deposition.
[0024] The present invention further provides a lithium ion battery comprising the negative electrode material described above.
[0025] Beneficial effects of the present invention:
[0026] The key point of the present invention is to use ultrafast ultrahigh temperature sintering technology to perform final treatment on porous carbon materials, and at the same time add seed inducer to promote graphitization of porous carbon materials during sintering. 3 -10 4℃ / min) and high cooling rates (up to 10 4 ℃ / min) and high sintering temperature (up to 3000℃), its ultra-high heating rate and ultra-high temperature can reduce the ultra-fast sintering time to minutes (30s-600s). These advantages enable the seed inducer to fully play its role and promote the graphitization of porous carbon materials. On the other hand, high temperature and short holding time of minutes can also promote the closure of micropores less than 2nm in porous carbon materials, increase the proportion of mesopores with pore size of 2-10nm, and thus improve the conductivity of porous carbon materials. At the same time, suitable pore size is more conducive to the deposition of nano-scale materials, improving the deposition efficiency and effect of deposited materials.
[0027] In addition, the preparation method of the present invention uses a seed inducer in combination with ultrafast ultrahigh temperature sintering technology, which will not introduce impurities into the material and does not require subsequent acid washing, water washing and other steps. It not only simplifies the process flow and improves production efficiency, but is also environmentally friendly and very suitable for industrial applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 Schematic diagram of the preparation of porous carbon material in a preferred embodiment of the present invention.
[0029] Figure 2 1 is the Raman spectrum of the porous carbon material prepared in Example 1 and Comparative Examples 1-2 of the present invention. DETAILED DESCRIPTION
[0030] Embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention.
[0031] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0032] The first aspect of the present invention provides a method for preparing a porous carbon material. In the present invention, a carbon precursor and a seed inducer are mixed and then subjected to carbonization and physical activation processes to obtain a porous carbon precursor material, which is then sintered using ultrafast and ultrahigh temperature sintering technology to obtain a porous carbon material with a high degree of graphitization and a high proportion of mesopores (pore size 2-10nm). The porous carbon material has excellent electrical conductivity, and the high proportion of mesopores is conducive to the subsequent deposition of active materials such as silicon carbon in its pores, thereby solving the deposition problem caused by the low electrical conductivity of the porous carbon matrix and the high proportion of micropores with a pore size of less than 2nm.
[0033] The main steps for preparing the porous carbon material in the present invention are as follows:
[0034] S1. Providing a mixed slurry containing a carbon precursor and a seed crystal inducing agent, and carbonizing the mixed slurry to obtain a pre-carbonized precursor material.
[0035] The porous carbon material described in this article refers to a carbon material with different pore structures. Depending on the source of the carbon material, it can be biomass porous carbon or resin porous carbon. Porous carbon materials can be used as matrix materials. Different pore structures allow different molecules / ions to enter the pores, so they can provide a matrix for the deposition and attachment of active materials, and are suitable for preparing new lithium-ion battery negative electrode materials.
[0036] The carbon precursor described herein refers to the carbon-containing organic matter before the carbonization of the porous carbon material, which can be a biomass carbon source or a resin carbon source. For biomass carbon sources, the carbon precursor can be, for example, at least one of coconut shells, straws, bamboo, rice husks, wood, bagasse, and nut shells, but is not limited thereto; for resin carbon sources, the carbon precursor can be, for example, at least one of furan resins, urea-formaldehyde resins, pyrimidine resins, phenolic resins, epoxy resins, polyoxymethylene methyl acrylate resins, and polyacrylonitrile, but is not limited thereto. In some specific implementation cases of the present invention, the carbon precursor is selected from one or a mixture of two or more of phenolic resins, coconut shells, straws, and bamboos.
[0037] The principle of seed induction is to provide seed crystals of known structure, combined with appropriate growth conditions and control means to achieve the purpose of significantly accelerating crystal growth. The seed inducer described herein refers to a substance used to promote crystal growth during the crystallization process, which can accelerate crystal growth, help control the shape, size and structure of the crystal, thereby improving the quality of the final product. The role of the seed inducer in this article is that during the formation of porous carbon, the precursor material is assembled with the seed inducer through hydrogen bonds, and plays a role of sequential induction during the carbonization process to improve the crystal properties of the final porous carbon material. In the present invention, the seed inducer selects an enantiomer with the same crystal form or stereo configuration as the porous carbon material, and preferably selects a substance with a structure similar to the porous carbon material, such as a substance homogeneous with the carbon precursor, that is, a carbon material, such as graphene oxide, graphene, carbon nanotubes, carbon fibers, at least one, preferably, the seed inducer is graphene oxide.
[0038] It can be understood that the amount of seed inducer added can be selected or optimized based on the amount of carbon precursor used using methods known in the art. In some specific embodiments of the present invention, the mass ratio of carbon precursor to seed inducer is 20:1~300:1, for example, it can be any ratio of 20:1, 50:1, 80:1, 100:1, 150:1, 200:1, 300:1, etc. Preferably, the mass ratio of carbon precursor to seed inducer is 50:1~100:1.
[0039] The mixed slurry described herein is obtained by dispersing a carbon precursor and a seed inducer in a suitable solvent, wherein the solvent is selected based on the following criteria: (1) being inert to the carbon precursor and the seed inducer, i.e., not reacting with the carbon precursor and the seed inducer; (2) being volatile and harmless, i.e., being easy to remove later. In some specific implementation cases of the present invention, the solvent may be water, or an organic solvent such as ethanol or isopropanol.
[0040] In some embodiments of the present invention, the mixed slurry is solidified, crushed, dried, and carbonized to obtain a pre-carbonized precursor material. Among them, the solidification, crushing, and drying can be carried out in a manner known in the art, subject to the drying of the material. The carbonization process and parameters can be confirmed according to the type of carbon precursor and the conditions known in the art. In some specific implementation cases of the present invention, the carbonization is carried out in an inert atmosphere (such as nitrogen or a rare gas), the temperature is 300~800°C, the insulation time is 1~8h, and the heating rate is 1~20°C / min; preferably, the carbonization temperature is 300~600°C, the insulation time is 2~6h, and the heating rate is 3~10°C / min.
[0041] S2, physically activating the pre-carbonized precursor material to form pores, thereby obtaining a porous carbon precursor material.
[0042] The pre-carbonized precursor material obtained in step S1 is activated and pore-formed by a physical activation method known in the art to obtain a porous carbon precursor material.
[0043] The physical activation method described in this article uses water vapor, CO2 and other gases as activators to activate and form pores in the pre-carbonized precursor material at high temperature.
[0044] During the specific operation, firstly, an inert atmosphere is introduced to expel the air in the reaction system, and then the air is replaced with an activating gas to activate and form pores. The specific activation temperature, time and activating agent flux can be optimized or adjusted according to the product needs based on methods known in the art. In some specific implementation cases of the present invention, the activation temperature is 800-1300°C, for example, it can be 800°C, 850°C, 900°C, 1000°C, 1100°C, 1200°C or 1300°C. Preferably, the activation temperature is 850-900°C; the activation time is 0.5-6h, for example, it can be 0.5h, 0.75h, 1h, 1 .5h, 2h, 2.5h, 3h, 4h, 5h or 6h, preferably, the activation time is 1.5~3h; the flux of the gas activator is 0.1~20L / min, for example, it can be 0.1L / min, 0.5L / min, 1L / min, 2L / min, 3L / min, 4L / min, 5L / min, 10L / min, 15L / min or 20L / min, preferably, the flux of the gas activator is 10~20L / min.
[0045] It is understood that after activation, the product is further washed, dried and crushed to obtain a porous carbon precursor material of suitable particle size. The specific washing, drying and crushing steps are well known in the art and will not be described here. In some specific implementation cases of the present invention, the particle size Dv50 of the porous carbon precursor material is 5 μm to 8 μm.
[0046] S3. Sintering the porous carbon precursor material by ultrafast ultrahigh temperature sintering technology to obtain a porous carbon material.
[0047] Ultrafast ultrahigh temperature sintering technology has extremely high heating and cooling rates, and can complete the sintering process within a few seconds to tens of seconds, which can significantly shorten the material preparation time, reduce the loss of volatile elements, and improve the density and performance of the material. The ultrafast ultrahigh temperature sintering technology described in this article mainly refers to ultrafast Joule heating. Using the Joule thermal effect, the heating elements are upper and lower carbon materials (such as carbon bars, graphite felt, carbon paper, carbon cloth, etc.), and the material to be sintered is placed between the upper and lower carbon materials. The current passes through the conductor to form a high-temperature temperature field between the upper and lower carbon materials, and the heat is conducted to the material to be sintered through radiation, so that the material is sintered and densified.
[0048] In the present invention, the porous carbon precursor material is sintered by ultrafast ultrahigh temperature sintering technology. After the precursor material and the seed inducer are assembled by hydrogen bonds, during the carbonization process, the aromatic rings near the seed inducer tend to be arranged along the graphene layer, making the sp 3 Hybridized carbon to sp 2conversion, reduces defects and improves the degree of graphitization; the ultra-fast heating rate and high temperature of the ultra-fast ultra-high temperature sintering technology close the micropores, while reducing the collapse of the mesoporous structure, promoting the graphitization of carbonaceous materials, reducing the increase of micropores at high temperatures, increasing the proportion of mesopores, and improving the electrical conductivity of porous carbon materials, providing excellent conditions for the subsequent deposition of nano-scale active materials as a matrix.
[0049] The heating rate of ultra-fast Joule heating is generally 10 3 ~10 4 ℃ / min. In some specific implementation cases of the present invention, sintering is carried out in an inert atmosphere, and the sintering temperature is 1000~3500℃, for example, it can be 1000℃, 1500℃, 2000℃, 2500℃, 3000℃ or 3500℃. Preferably, the sintering temperature is 1000~2500℃; the heating time is 5~30s, for example, it can be 5s, 10s, 15s, 20s, 25s or 30s; the sintering time is 30~600s, for example, it can be 30s, 60s, 90s, 120s, 150s, 180s, 210s, 240s, 300s, 360s, 450s or 600s. It is understandable that the sintering temperature, sintering time, heating time, etc. can be adjusted or optimized according to the final product structure or performance using methods known in the art. In the present invention, the above conditions can be controlled by adjusting the voltage and current conditions of Joule heating without special limitations.
[0050] The second aspect of the present invention provides a porous carbon material, which is prepared by the preparation method described above. The porous carbon material has a high degree of graphitization and a high electrical conductivity, which can be as high as 32.7 (S / cm). At the same time, the proportion of micropores smaller than 2nm is small, with a minimum of only 5.2%.
[0051] The third aspect of the present invention provides a negative electrode material, which contains the porous carbon material prepared by the preparation method described above. The negative electrode material uses the porous carbon material as a matrix, and contains active materials in the pores of the porous carbon material.
[0052] The active material described in this article can adopt the negative electrode active material well known in the field of lithium ion battery negative electrode materials. Preferably, the active material contains silicon-carbon material, wherein the silicon-carbon material is deposited in the pores of the porous carbon material by a vapor deposition method well known in the art. Since the porous carbon material has high electrical conductivity and a high proportion of mesopores, the deposition efficiency and deposition effect of the active material in the porous carbon material can be improved, so that a lithium ion battery negative electrode material with excellent performance can be obtained.
[0053] It is understood that the preparation of the negative electrode material described herein can adopt methods known in the art, and the specific process conditions can be adjusted as needed. In some specific embodiments of the present invention, the porous carbon material described above is used as a matrix, and nano-silicon deposition and surface carbon layer coating are successively performed by chemical vapor deposition. The intake parameters of the deposited silicon source gas and the carbon source gas and the deposition time can be adjusted to obtain a lithium ion battery negative electrode material based on porous carbon. Among them, in the nano-silicon deposition stage, a silicon source gas and an inert gas mixture are selected as the main gas, and the silicon source gas includes one or more of monosilane, disilane, trisilane, monochlorosilane, dichlorosilane and trichlorosilane. The deposition temperature is preferably 400~600℃, the gas pressure is 0.1~0.8MPa, and the deposition time is 1~8h. After completing the deposition stage, the silicon source gas is switched to a mixture of carbon source gas and inert gas for surface coating, wherein the carbon source gas includes one or a mixture of two or more of methane, ethane, butane, propane, ethylene, propylene, butene, and acetylene, the deposition temperature is 500~700°C, the gas pressure is 0.1~0.8MPa, and the deposition time is 1~4h.
[0054] The present invention also provides a lithium ion battery, which contains the negative electrode material described above. Due to the advantages of the porous carbon material in the negative electrode material, the lithium ion battery containing it has excellent electrochemical performance, improves the conductivity and rate performance while maintaining the first cycle coulomb efficiency, and also increases the cycle performance of the battery.
[0055] The present invention is described below by means of specific examples. It should be noted that the following specific examples are only for illustrative purposes and do not limit the scope of the present invention in any way. In addition, unless otherwise specified, methods without specific conditions or steps are conventional methods, and the reagents and materials used can be obtained from commercial channels.
[0056] Example 1
[0057] This embodiment provides a method for preparing a porous carbon material. The process can be found in Figure 1 , the specific steps are as follows:
[0058] S1. According to the mass ratio of phenolic resin to graphene oxide being 50:1, phenolic resin is added to the aqueous suspension of graphene oxide and mixed evenly, solidified, crushed and dried, and heated to 600°C in a tubular furnace in an argon atmosphere at a heating rate of 5°C / min and kept warm for 2h to obtain a pre-carbonized precursor material.
[0059] S2. Continue to heat the pre-carbonized precursor material to 900°C, replace the introduced argon gas with water vapor (gas flux of 15 L / min), activate for 1.5 hours, and then cool to room temperature. Wash and dry the resulting product, and grind it with air flow to obtain a porous carbon precursor material with a particle size satisfying Dv50 of 5μm to 8μm.
[0060] S3. Using ultra-fast Joule heating to heat the porous carbon precursor material from room temperature to 2500° C. for 10 seconds, and sintering at 2500° C. for 1 minute to obtain a porous carbon material.
[0061] Example 2
[0062] This example provides another method for preparing porous carbon materials. The process can be found in Figure 1 , the specific steps are as follows:
[0063] S1. According to the mass ratio of coconut shell to graphene being 50:1, coconut shell is added to the aqueous suspension of graphene and mixed evenly, solidified, crushed and dried, and heated to 600°C in a tubular furnace in an argon atmosphere at a heating rate of 5°C / min and kept warm for 2h to obtain a pre-carbonized precursor material.
[0064] S2. Continue to heat the pre-carbonized precursor material to 900°C, replace the introduced argon gas with water vapor (gas flux of 15 L / min), activate for 1.5 hours, and then cool to room temperature. Wash and dry the resulting product, and grind it with air flow to obtain a porous carbon precursor material with a particle size satisfying Dv50 of 5μm to 8μm.
[0065] S3. Using ultra-fast Joule heating to heat the porous carbon precursor material from room temperature to 2500° C. for 10 seconds, and sintering at 2500° C. for 1 minute to obtain a porous carbon material.
[0066] Example 3
[0067] This example provides another method for preparing porous carbon materials. The process can be found in Figure 1 , the specific steps are as follows:
[0068] S1. According to the mass ratio of phenolic resin to graphene oxide being 50:1, phenolic resin is added to the aqueous suspension of graphene oxide and mixed evenly, solidified, crushed and dried, and heated to 600°C in a tubular furnace in an argon atmosphere at a heating rate of 5°C / min and kept warm for 2h to obtain a pre-carbonized precursor material.
[0069] S2. Continue to heat the pre-carbonized precursor material to 900°C, replace the introduced argon gas with water vapor (gas flux of 15 L / min), activate for 1.5 hours, and then cool to room temperature. Wash and dry the resulting product, and grind it with air flow to obtain a porous carbon precursor material with a particle size satisfying Dv50 of 5μm to 8μm.
[0070] S3. Using ultra-fast Joule heating to heat the porous carbon precursor material from room temperature to 1500° C. in 6 seconds, and sintering at 1500° C. for 1 minute to obtain a porous carbon material.
[0071] Example 4
[0072] This example provides another method for preparing porous carbon materials. The process can be found in Figure 1 , the specific steps are as follows:
[0073] S1. According to the mass ratio of straw powder to carbon nanotubes being 80:1, the straw powder is added to the ethanol suspension of carbon nanotubes and mixed evenly, solidified, crushed and dried, and heated to 600°C in a tubular furnace in an argon atmosphere at a heating rate of 5°C / min and kept warm for 2h to obtain a pre-carbonized precursor material.
[0074] S2. Continue to heat the pre-carbonized precursor material to 850°C, replace the introduced argon gas with water vapor (gas flux of 15 L / min), activate for 3 hours, and then cool to room temperature. Wash and dry the resulting product, and grind it with air flow to obtain a porous carbon precursor material with a particle size satisfying Dv50 of 5μm to 8μm.
[0075] S3. Using ultra-fast Joule heating to heat the porous carbon precursor material from room temperature to 2000° C. for 10 seconds, and sintering at 2000° C. for 1 minute to obtain a porous carbon material.
[0076] Example 5
[0077] This example provides another method for preparing porous carbon materials. The process can be found in Figure 1 , the specific steps are as follows:
[0078] S1. According to the mass ratio of bamboo powder to carbon fiber being 100:1, bamboo powder is added to the isopropanol suspension of carbon fiber and mixed evenly, solidified, crushed and dried, and heated to 600°C at a heating rate of 5°C / min in a tubular furnace in an argon atmosphere and kept warm for 2 hours to obtain a pre-carbonized precursor material.
[0079] S2. Continue to heat the pre-carbonized precursor material to 880°C, replace the introduced argon gas with water vapor (gas flux of 15 L / min), activate for 2 hours, and then cool to room temperature. Wash and dry the resulting product, and grind it with air flow to obtain a porous carbon precursor material with a particle size satisfying Dv50 of 5μm to 8μm.
[0080] S3. Using ultra-fast Joule heating to heat the porous carbon precursor material from room temperature to 1000° C. for 10 seconds, and sintering at 1000° C. for 1 minute to obtain a porous carbon material.
[0081] Comparative Example 1
[0082] This comparative example provides a method for preparing a porous carbon material, which adopts the same implementation as in Example 1, except that the sintering treatment in step S3 is not performed. The other steps and process conditions are the same as in Example 1.
[0083] The steps for preparing the porous carbon material in this comparative example are as follows:
[0084] S1. According to the mass ratio of phenolic resin to graphene oxide being 50:1, phenolic resin is added to the aqueous suspension of graphene oxide and mixed evenly, solidified, crushed and dried, and heated to 600°C in a tubular furnace in an argon atmosphere at a heating rate of 5°C / min and kept warm for 2h to obtain a pre-carbonized precursor material.
[0085] S2. Continue to heat the pre-carbonized precursor material to 900°C, replace the introduced argon gas with water vapor (gas flux of 15 L / min), activate for 1.5 hours, and then cool to room temperature. Wash and dry the resulting product, and grind it with air flow to obtain a porous carbon precursor material with a particle size satisfying Dv50 of 5μm to 8μm.
[0086] Comparative Example 2
[0087] This comparative example provides a method for preparing a porous carbon material, which adopts the same implementation as in Example 1, except that: in step S1, no seed inducer graphene oxide is added. Other steps and process conditions are the same as in Example 1.
[0088] S1. Add phenolic resin into water and mix evenly, solidify, crush and dry, heat to 600° C. at a heating rate of 5° C. / min in a tube furnace in an argon atmosphere and keep the temperature for 2 h to obtain a pre-carbonized precursor material.
[0089] S2. Continue to heat the pre-carbonized precursor material to 900°C, replace the introduced argon gas with water vapor (gas flux of 15 L / min), activate for 1.5 hours, and then cool to room temperature. Wash and dry the resulting product, and grind it with air flow to obtain a porous carbon precursor material with a particle size satisfying Dv50 of 5μm to 8μm.
[0090] S3. Using ultra-fast Joule heating to heat the porous carbon precursor material from room temperature to 2500° C. for 10 seconds, and sintering at 2500° C. for 1 minute to obtain a porous carbon material.
[0091] Comparative Example 3
[0092] This comparative example provides a method for preparing a porous carbon material, which adopts the same implementation as in Example 1, except that a conventional graphite furnace is used for sintering in step S3. Other steps and process conditions are the same as in Example 1.
[0093] The steps for preparing the porous carbon material in this comparative example are as follows:
[0094] S1. According to the mass ratio of phenolic resin to graphene oxide being 50:1, phenolic resin is added to the aqueous suspension of graphene oxide and mixed evenly, solidified, crushed and dried, and heated to 600°C in a tubular furnace in an argon atmosphere at a heating rate of 5°C / min and kept warm for 2h to obtain a pre-carbonized precursor material.
[0095] S2. Continue to heat the pre-carbonized precursor material to 900°C, replace the introduced argon gas with water vapor (gas flux of 15 L / min), activate for 1.5 hours, and then cool to room temperature. Wash and dry the resulting product, and grind it with air flow to obtain a porous carbon precursor material with a particle size satisfying Dv50 of 5μm to 8μm.
[0096] S3. Using a graphite furnace, the temperature of the porous carbon precursor material is raised from room temperature to 2500° C. at a rate of 20° C. / min, and kept at 2500° C. for 2 h to obtain a porous carbon material.
[0097] Performance Testing
[0098] 1. The porous carbon materials in Examples 1-5 and Comparative Examples 1-3 were tested for electrical conductivity and pore size distribution, respectively, wherein the electrical conductivity was calculated after testing using a four-probe method; the pore size distribution was obtained after BET testing and analysis using a gas adsorption instrument (Autosorb-IQ3), and the results are shown in Table 1.
[0099] Table 1 Electrical conductivity and pore distribution results of porous carbon materials
[0100]
[0101] also, Figure 2 The Raman spectra of the porous carbon materials in Example 1 and Comparative Examples 1-2 are shown in FIG. Figure 2 It can be seen that:
[0102] When a seed inducer is added during the preparation of porous carbon materials, their electrical conductivity increases, indicating that their degree of graphitization is improved.
[0103] from Figure 2 It can be seen that if the ultrafast ultrahigh temperature sintering technology is not used for re-carbonization, the degree of graphitization will be reduced, resulting in a significant decrease in its conductivity; and if the seed inducer is not added, the degree of graphitization is reduced compared with Example 1, and its conductivity will also be reduced to a certain extent.
[0104] Due to the use of ultrafast high-temperature sintering technology, the electrical conductivity in Example 1 is nearly 1 times higher than that in Comparative Example 3, indicating that ultrafast high-temperature sintering technology can effectively improve the degree of graphitization and improve electrical conductivity; at the same time, it can be seen that the micropores of the porous carbon material with a size less than 2nm after ultrafast high-temperature sintering can be effectively closed.
[0105] Based on the above results, it can be seen that thanks to the rapid response of ultrafast and ultrahigh temperature sintering technology and the addition of seed inducers, the degree of graphitization of porous carbon during the sintering preparation process is improved, thereby improving the electrical conductivity of the material. At the same time, the tiny pores with side effects are closed, laying the foundation for the subsequent preparation of silicon-carbon composite negative electrode materials based on porous carbon.
[0106] 2. Test the application of the porous carbon material in the present invention in negative electrode materials.
[0107] First, the porous carbon materials in Example 1 and Comparative Examples 1 to 3 were prepared by the following methods to obtain silicon-carbon composite negative electrode materials:
[0108] A mixed gas of monosilane and argon in a volume ratio of 5:1 was introduced into the CVD furnace to deposit silicon into the modified porous carbon matrix at a deposition temperature of 480°C for 2 h. The gas was then converted into a mixed gas of acetylene and argon in a volume ratio of 3:1 for surface carbon coating at a deposition temperature of 600°C for 2 h.
[0109] A half-cell was assembled with a lithium sheet as the positive electrode and the silicon-carbon composite negative electrode material obtained above as the negative electrode, the electrolyte was 302 electrolyte (1M LiPF6, EC / DEC), and the separator was PP. The half-cells containing the porous carbon materials in Example 1 and Comparative Examples 1-3 were respectively recorded as Batteries 1~4.
[0110] The BTS2000 test system was used to test the above half-cell. The assembled battery was discharged to 5mV in the first week according to 0.5C, 0.1C, and 0.05C steps, and charged to 1.5V at 0.1C constant current. In the second week, the battery was discharged to 5mV in 0.5C, 0.1C, and 0.05C steps, and charged to 1.5V at 1C constant current. Subsequently, the battery was charged and discharged at 1C / 1C for 20 cycles, and the test temperature was 25°C. The test results are shown in Table 2.
[0111] Table 2 Performance of half-cell
[0112]
[0113] From the test results in Table 2, it can be seen that the first cycle coulombic efficiency, conductivity and rate performance of battery 1 are better than those of batteries 2 to 4, and its cycle performance is also improved to a certain extent compared with batteries 2 to 4. This is mainly due to the ultrafast ultra-high temperature sintering technology combined with the porous carbon preparation process of the seed inducer to produce a porous carbon material with a high degree of graphitization and a high proportion of mesopores, which effectively improves the electrochemical performance of the negative electrode material, and then improves the electrochemical performance of the lithium-ion battery.
[0114] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0115] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a porous carbon material, characterized in that: The following steps are involved: Providing a mixed slurry containing a carbon precursor and a seed inducer, and carbonizing the mixed slurry to obtain a pre-carbonized precursor material; the seed inducer is selected from one or a mixture of two or more of graphene oxide, graphene, carbon nanotubes, and carbon fibers; Physically activating the pre-carbonized precursor material to form pores, thereby obtaining a porous carbon precursor material; The porous carbon precursor material is sintered by adopting ultrafast ultrahigh temperature sintering technology to obtain the porous carbon material.
2. The preparation method according to claim 1, characterized in that The carbon precursor is a biomass carbon source or a resin carbon source; Wherein, the biomass carbon source is selected from one or a mixture of two or more of coconut shells, straw, rice husks, wood, bamboo, bagasse, and nut shells; The resin carbon source is selected from one or a mixture of two or more of furan resin, urea-formaldehyde resin, pyrimidine resin, phenol-formaldehyde resin, epoxy resin, polyoxymethylene methyl acrylate resin and polyacrylonitrile.
3. The preparation method according to claim 1, characterized in that: The mass ratio of the carbon precursor to the seed inducer is 20:1-300:
1.
4. The preparation method according to claim 1, characterized in that: The gas activator used in the physical activation is water vapor or CO2; And / or, the temperature of the physical activation is 800° C. to 1300° C., the activation time is 0.5 h to 6 h, and the flux of the gas activator is 0.1 L / min to 20 L / min.
5. The preparation method according to claim 1, characterized in that: The temperature of the ultrafast ultrahigh temperature sintering technology is 1000°C~3500°C, the heating time is 5s~30s, and the sintering time is 30s~600s.
6. A porous carbon material, characterized in that: The method is prepared according to any one of claims 1 to 5.
7. A negative electrode material, characterized in that: It comprises a porous carbon material prepared by the preparation method according to any one of claims 1 to 5; the pores of the porous carbon material contain active materials.
8. The negative electrode material according to claim 7, characterized in that The negative electrode material is a silicon-carbon composite material, and the active material is a silicon-carbon material; And / or, the silicon carbon material is deposited in the pores of the porous carbon material by vapor deposition.
9. A lithium ion battery, characterized in that: Contains the negative electrode material according to claim 7 or 8.
Citation Information
Patent Citations
Preparation method of porous carbon
CN104817067A
High-electric-conductivity phenolic-resin-based graphene-modified activated carbon, and preparation method and application thereof
CN110316733A
Cobalt disulfide / boron nitrogen sulfur co-doped porous carbon composite material and preparation method and application thereof
CN115939341A
Method for preparing carbon nanospheres through Joule thermal flash evaporation and application
CN117585667A
Porous carbon-silicon composite negative electrode material and preparation method thereof
CN117638045A
